Inklusi sebagai Dimensi Etika Kerja Modern: Implikasinya terhadap Kinerja dan Kesejahteraan SDM Perguruan Tinggi - Florensia Florensia; Arya Budi Sutopo; Amanah Rahmadhani; Balqis Fadhillah I.P; Locita Dara R; Amanda Indah N.A (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
In higher education, the level of lecturer involvement in decision-making and professional development varies. Some lecturers feel unappreciated or not fully involved, which impacts their morale, collaboration, and sense of well-being. This study aims to analyze how the implementation of inclusive workplace policies can affect lecturers' work outcomes and well-being. The method used was descriptive-analytical literature research, collecting and analyzing scientific articles and journals published in the last five years that are relevant to the academic world. The results show that an inclusive work environment can improve work morale, creativity, and collaboration among lecturers. An inclusive environment also makes lecturers feel psychologically safe and open to communication. Furthermore, an inclusive environment also reduces stress and conflict among colleagues, thereby improving the physical and mental well-being of lecturers. These findings suggest that inclusiveness is not only an ethical principle but also an effective way to improve performance, engagement, and quality of work life in academic environments.